Evaluación de la vacuna parasitaria (Strongyloides) en ovinos. - Acuña Cajamarca, Brigette Naomi (2023)
The main objective of this research is the evaluation of a parasite vaccine for Strongyloides in sheep through serological tests (Ig A, Ig E, hematological examinations) and coproparasitic tests to establish its efficacy. The present study was carried out in the Quinticusig neighborhood, Sigchos canton, province of Cotopaxi, evaluating 22 Creole breed sheep between the ages of 8 months and 4 years old. Based on this, an analysis of each of the animals under study was carried out to determine the prevalence of Strongyloides post inoculation and to check the health status of each of the animals. Subsequently, the data analysis was carried out with T-Student with a randomized design. It was verified that 81.81% of the population had presence of Strongyloides with no significant difference between age and sex, 4.54% of the population had elevated IgE, and 27.27% had elevated IgA, which reflects the presence of Strongyloides in the intestinal mucosa. As for the hematological examination, 63.63% presented normocytic anemia. In conclusion, it was determined that the presence of Strongyloides post inoculation did not have a significant increase in the experimental units. The beneficiaries of the research are families dedicated to commercial family sheep breeding.